A Review on Pragmatism-Philosophy: Project-Based Learning in Grammar Teaching - Tri Cantika Putri (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The challenge of teaching English grammar in Indonesia, aggravated by evolving curricula and the concept of “Merdeka Belajar,” compels the teachers to adapt more creative and critical teaching methods. This study evaluates the effectiveness of Project-Based Learning (PjBL) as a promising method for enhancing grammar learning. Grounded in pragmatism-philosophy of John Dewey perspectives, the research aims to recognize the significance of creating an optimal teaching-learning process. Utilizing document analysis, the study delves into five article which discussing PjBL in grammar teaching. The findings offer valuable insights that bridge traditional pedagogy with today’s school needs. By highlighting the transformative potential of grammar teaching, this research supports teachers in navigating the ever-changing of language teaching.